Цифрова держава в контексті правової реформи в Україні: теоретико-правовий аспект - Наджафлі, Е. М.; Nadzhafli, E. M. (Право і безпека. – 2022. – № 2 (85). – С. 202-217, 2022)
Дослідження присвячено вивченню теоретико-правових аспектів формування цифрової держави, що є невід’ємним елементом дигіталізації всіх сфер суспільного життя та вимогою сучасності. Встановлено, що правову реформу в галузі формування цифрової держави слід визнати таким різновидом правової реформи, який спрямовується на цілісне, комплексне змінення умов та правової основи організації і функціонування апарату держави з метою спрощення системи державного управління, суттєвого підвищення його ефективності. Актуальною потребою на сьогодні слід визнати перехід від екстенсивної парадигми формування цифрової держави до інтенсивної яка б передбачала інклюзивну модель формування цифрової держави завдяки реальному залученню до вирішення державних справ інститутів громадянського суспільства, стимулювала громадянську ініціативу та унеможливлювала прийняття ключових правових актів без попереднього громадського обговорення.

The purpose of the article is theoretical and legal coverage of the key parameters of legal reform in the field of digital state formation based on the application of the institutional approach, as well as taking into account the achievements of domestic theoretical and legal science and legal branch science. It is shown that the formation of a digital state is an integral element of digitalization of all spheres of social life and a requirement of modernity. Structural and procedural approaches to the study of legal reform in the field of digital state formation are analyzed. The expediency of combining these approaches for a deeper and more comprehensive scientific knowledge of the studied phenomenon is highlighted. It has been established that the legal reform in the field of the formation of a digital state should be recognized as a type of legal reform aimed at a holistic, comprehensive change in the conditions and legal basis of the organization and functioning of the state apparatus in the direction of its optimization and the widest application of information and communication technologies in order to simplify the state administration system, significantly increasing its effectiveness and including society and individual citizens in solving the most significant issues of social and state life. The key aspects and directions of this reform are analyzed. It has been proven that the model of forming an exclusive digital state, which did not provide for the wide involvement of society and its institutions in solving national (public) issues and affairs, has been implemented in modern Ukraine, which essentially reproduced the conservative trajectory of the previous state-power development. It is indicated that the transition from an extensive paradigm of a digital state formation to an intensive one should be recognized as an urgent need today, which would provide for an inclusive model of the formation of a digital state due to the real inclusion (involvement) of civil society institutions in solving state affairs, stimulating civil initiative and making it impossible to adopt key legal acts without prior extensive public consultation, which should be given not optional but mandatory character.

Исследование посвящено изучению теоретико-правовых аспектов формирования цифрового государства, являющегося неотъемлемым элементом диджитализации всех сфер общественной жизни и требованием современности. Установлено, что правовую реформу в области формирования цифрового государства следует признать таким видом правовой реформы, который направлен на целостное, комплексное изменение условий и правовой основы организации и функционирования аппарата государства с целью упрощения системы государственного управления, существенного повышения его эффективности. Актуальной потребностью настоящего следует признать переход от экстенсивной парадигмы формирования цифрового государства к интенсивной, которая предусматривала бы инклюзивную модель формирования цифрового государства за счет реального привлечения к решению государственных дел институтов гражданского общества, стимулировала гражданскую инициативу и делала невозможным принятие ключевых правовых актов без предварительного общественного обсуждения.
Digital state in the context of legal reform in Ukraine: theoretical and legal aspect
Цифровое государство в контексте правовой реформы в Украине: теоретико-правовой аспект
Наджафлі, Е. Цифрова держава в контексті правової реформи в Україні: теоретико-правовий аспект / Емін Наджафлі // Право і безпека. – 2022. – № 2 (85). – С. 202-217. – DOI: https://doi.org/10.32631/pb.2022.2.19.
Наджафлі Е. Цифрова держава в контексті правової реформи в Україні: теоретико-правовий аспект. Право і безпека. 2022. No 2 (85). С. 202–217. DOI: https://doi.org/10.32631/pb.2022.2.19.
Najafli, E. (2022). Digital state in the context of legal reform in Ukraine: theoretical and legal aspect. Law and Safety, 2(85), 202–217. https://doi.org/10.32631/pb.2022.2.19.
Keywords: Держава і право. State and Law. Государство и право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; дигіталізація; інформаційне суспільство; цифрова держава; ексклюзивна парадигма; інклюзивна парадигма; digitization; information society; digital state; inclusive paradigm; exclusive paradigm; диджитализация; информационное общество; цифровое государство